The effect of precision and power grips on activations in human auditory cortex - Wikman, Patrik A.; Vainio, Lari; Rinne, Teemu (Frontiers in Neuroscience, 2015)
The neuroanatomical pathways interconnecting auditory and motor cortices play a key role in current models of human auditory cortex (AC). Evidently, auditory-motor interaction is important in speech and music production, but the significance of these cortical pathways in other auditory processing is not well known. We investigated the general effects of motor responding on AC activations to sounds during auditory and visual tasks. During all task blocks, subjects detected targets in the designated modality, reported the relative number of targets at the end of the block, and ignored the stimuli presented in the opposite modality. In each block, they were also instructed to respond to targets either using a precision grip, power grip, or to give no overt target responses. We found that motor responding strongly modulated AC activations. First, during both visual and auditory tasks, activations in widespread regions of AC decreased when subjects made precision and power grip responses to targets. Second, activations in AC were modulated by grip type during the auditory but not during the visual task. Further, the motor effects were distinct from the strong attention-related modulations in AC. These results are consistent with the idea that operations in AC are shaped by its connections with motor cortical regions.